Tinjauan Yuridis Peran Koperasi Merah Putih dalam Penguatan Ekonomi dan Kesejahteraan Masyarakat Desa - Suyanto Suyanto; Arjuna Raenaldi (CV. Rumoh Aceh Publishing, 2026)
This research aims to analyze the legal standing and effectiveness of the Merah Putih Cooperative in improving the economic welfare of rural communities. As a grassroots economic institution, cooperatives hold a strategic role regulated under Law Number 25 of 1992 concerning Cooperatives. The research method employed is normative juridical with a statutory and literature review approach. The results indicate that the Merah Putih Cooperative has fulfilled the legality aspects as a legal entity; however, its implementation still faces challenges regarding member participation and lack of transparency in governance. Juridically, strengthening supervisory functions and cooperative education are key to ensuring cooperatives function as the backbone of the village economy. This study concludes that legal certainty in capital management and the fair distribution of Remaining Business Results (SHU) significantly influences public trust. Synergy between cooperative management and village government is required to optimize local economic potential through an independent and accountable cooperative framework.